A polyacrylonitrile coated copper-doped manganese-based Prussian blue positive electrode material and its preparation method and application

Through the preparation method of polyacrylonitrile-coated copper-doped manganese-based Prussian blue positive electrode material, a uniform cladding layer is formed using radio frequency heating technology, which solves the problems of low electron conductivity and short cycle life of manganese-based Prussian blue positive electrode material, and significantly improves electrochemical performance and cycle stability.

CN119240744BActive Publication Date: 2025-04-04SHANDONG HAIHUA GRP CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411775088.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-04
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The existing manganese-based Prussian blue cathode materials have problems such as low electron conductivity, short cycle life and high potential polarization, and it is difficult to meet the commercial application standards.

Method used

The preparation method of polyacrylonitrile-coated copper-doped manganese-based Prussian blue positive electrode material is used to accurately control the crystal size and morphology of the material through radio frequency heating technology to form a uniform polyacrylonitrile coating to reduce internal stress and defects.

Benefits of technology

It significantly improves the electrochemical performance and cycle stability of the material, extends the cycle life, improves the redox activity of low-spin Fe2+/Fe3+, and achieves higher capacity contribution and better conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240744B_ABST
    Figure CN119240744B_ABST
Patent Text Reader

Abstract

The invention discloses a polyacrylonitrile-coated copper-doped manganese-based Prussian blue positive electrode material and a preparation method and application thereof, belonging to the field of sodium ion batteries. The synthesis method is novel, the process is simple and easy, and the controllability is strong. The doping of copper ions improves the structural stability of manganese-based Prussian blue and improves the low-spin Fe 2+ / Fe 3+ Coupled redox activation to obtain higher capacity contribution at a higher voltage; polyacrylonitrile as a coating layer can prevent the positive electrode material from being corroded by external substances such as oxygen and water vapor, resulting in high internal crystal water and Fe(CN)6 defect vacancy content; in addition, the use of radio frequency heating technology helps to form high-quality Prussian blue crystals, which is beneficial to improve the electrochemical performance of the material. This positive electrode material performs outstandingly in the application of sodium ion battery positive electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of sodium ion batteries, and specifically relates to a polyacrylonitrile-coated copper-doped manganese-based Prussian blue positive electrode material and a preparation method and application thereof. Background Art

[0002] The burning of fossil fuels has caused serious energy crises and environmental pollution problems, which has promoted the vigorous development of renewable energy such as wind and solar energy. Therefore, energy storage has become the key to the development of renewable energy and smart grids. Among various energy storage systems, sodium-ion batteries have similar electrochemical reaction mechanisms to lithium-ion batteries. Due to their abundant resources, low cost and environmental friendliness, they have become potential alternatives to energy storage systems. Among the many sodium-ion cathode materials, Prussian blue analogs (PBAs) have open framework structures, abundant redox active sites, strong structural stability, simple synthesis methods, excellent low-temperature performance and high specific capacity, which are very attractive in terms of development and application prospects. Among the many PBAs, the manganese-based Prussian blue (NMHFC) prepared by the Goodenough group has higher reversible capacity and average high potential than other analogs, which helps to achieve high energy storage, making NMHFC an ideal cathode material for rechargeable sodium-ion batteries.

[0003] However, due to the inherent low electronic conductivity of NMHFC, its cycle life is short, and high potential polarization occurs at high rates, so the performance of this material needs to be greatly improved before it can be put into commercial application. The Chinese patent document with publication number CN117239117A discloses a cation-doped manganese-based Prussian blue positive electrode material for sodium ion batteries and a preparation method thereof. The method is flexible and adjustable, simple and environmentally friendly, and has large-scale production capacity. The prepared positive electrode material has stable performance, but the battery specific capacity and cycle life do not meet the commercial application standards. This is because changes in various conditions during the preparation process may cause Fe(CN)6 to have more vacancies and higher coordinated water content. In order to improve the above defects, the Chinese patent document with publication number CN117133867A discloses a pyrrole-coated sodium ion Prussian blue positive electrode material and its preparation. The capacity retention rate of the sodium ion battery Prussian blue analog positive electrode has a significant improvement effect, but there is obvious high potential polarization at 1C current density, and the cycle life is low. Summary of the invention

[0004] The purpose of the present invention is to provide a polyacrylonitrile coated copper doped manganese-based Prussian blue positive electrode material and its preparation method and application, so as to solve the problems of the existing NMHFC with high internal crystal water and Fe(CN)6 defect vacancy content, Mn 2+ The preparation method of the present invention is original, the process is simple and easy, and the controllability is strong, which can significantly improve the electrochemical performance and cycle stability of the material.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing a polyacrylonitrile-coated copper-doped manganese-based Prussian blue positive electrode material, comprising the following steps:

[0007] (1) dissolving sodium ferrocyanide in deionized water, and adding a manganese source, a copper source, and a chelating agent thereto to obtain a precursor suspension;

[0008] (2) transferring the precursor suspension to a radio frequency heating device, performing moderate radio frequency heating treatment and aging, and then washing with a cleaning agent to obtain a Prussian blue wet material;

[0009] (3) Add the Prussian blue wet material obtained in step (2) to a solution of polyacrylonitrile in an organic solvent, continue to perform moderate radio frequency heating treatment, then centrifuge and vacuum dry, keep at room temperature for a period of time, and then grind to obtain a polyacrylonitrile-coated copper-doped manganese-based Prussian blue positive electrode material.

[0010] Preferably, in step (1), the manganese source is one of manganese chloride, manganese sulfate, manganese nitrate or manganese acetate, the copper source is one of copper sulfate, copper chloride or copper nitrate, and the chelating agent is one of ascorbic acid, citric acid, trisodium citrate or polyvinyl pyrrolidone; the ferrocyanide concentration is 0.1 to 0.5 mol / L, the manganese ion concentration is 0.05 to 0.2 mol / L, the molar ratio of copper ions to manganese ions is 1:1 to 9, and the molar ratio of manganese ions to chelating agent is 1:1 to 5.

[0011] Preferably, in step (2), the operating frequency of the radio frequency heating device is 700-900 kHz, the output current is 20-25 A, the reaction temperature is 60-90° C., the reaction time is 3-6 h, and the aging time is 2-6 h; the cleaning agent is water or ethanol.

[0012] Preferably, in step (3), the organic solvent is one of dimethylformamide, dimethyl sulfoxide or cyclopentane sulfone, and the mass of polyacrylonitrile accounts for 3% to 10% of the total mass of the polyacrylonitrile, Prussian blue wet material and the organic solvent; the operating frequency, output current, reaction temperature, reaction time and aging time of the radio frequency heating device are consistent with those of step (2); the centrifugal speed is 6000 to 12000 rpm, the drying temperature is 60 to 120°C, and the time is 6 to 10 hours; and it is maintained at room temperature for 6 to 24 hours.

[0013] In a second aspect, the present invention provides a polyacrylonitrile-coated copper-doped manganese-based Prussian blue positive electrode material, wherein the particle size of the positive electrode material is 0.22 to 1.37 μm, the atomic ratio of Mn to Cu is 0.95 to 9.10, the positive electrode material is in a cubic shape, and the grains have edges and corners.

[0014] In a third aspect, there is also provided an application of the polyacrylonitrile-coated copper-doped manganese-based Prussian blue positive electrode material prepared by the present invention for use in the positive electrode of a sodium ion battery.

[0015] The beneficial effects of the present invention are as follows:

[0016] 1. The present invention provides a method for preparing a polyacrylonitrile-coated copper-doped manganese-based Prussian blue positive electrode material, which shows significant advantages in the preparation process of Prussian blue by adopting radio frequency heating. The present invention can accurately control the size and morphology of Prussian blue crystals, promote or inhibit the phase change of the material, facilitate the uniform coating of the polyacrylonitrile coating layer, and reduce the stress and defects inside the Prussian blue material, thereby significantly improving the mechanical properties and overall stability of Prussian blue. Compared with traditional external heating methods, radio frequency heating can achieve uniform heating of the reaction system and avoid local overheating, thereby helping to generate high-quality Prussian blue crystals and significantly improving the electrochemical properties and cycle stability of the material.

[0017] 2. The preparation method of the polyacrylonitrile-coated copper-doped manganese-based Prussian blue positive electrode material provided by the present invention not only helps to reduce the overall cost of the positive electrode material and improve the economy of the battery by controlling the copper doping, but also, compared with other transition metal ion doping, the copper ion doping provides additional sodium ion storage sites and effectively reduces the dissolution of manganese ions in the electrolyte, thereby enhancing the structural stability of NMHFC and significantly improving the low-spin Fe 2+ / Fe 3+ The redox activity of the positive electrode material is enhanced, thereby promoting the insertion and deinsertion reaction of sodium ions and achieving a higher capacity contribution at a higher voltage. In addition, given the poor conductivity of polyacrylonitrile itself, the doping of copper ions increases the electronic conductivity and Na + The migration rate is improved, the conductive performance is improved, and then the high specific capacity of the sodium ion battery is improved.

[0018] 3. The polyacrylonitrile coated copper-doped manganese-based Prussian blue positive electrode material prepared by the present invention has higher oxidation resistance than metal oxides and carbon materials. The coating layer formed on the surface of the NMHFC material can prevent the NMHFC from being corroded by external substances such as oxygen and water vapor, resulting in a high content of internal crystal water and Fe(CN)6 defect vacancies; in addition, polyacrylonitrile as a coating layer can effectively prevent the deformation of the surface structure of the NMHFC, thereby avoiding the Mn 2+ Dissolved in liquid electrolyte, thus affecting the cycle reversibility and poor capacity retention.

[0019] 4. The polyacrylonitrile-coated copper-doped manganese-based Prussian blue cathode material prepared by the method of the present invention performs outstandingly in the application of sodium ion battery cathode. The specific capacities at current densities of 0.1, 0.2, 0.5, 1, 2 and 5C are 150.5-157.8, 130.2-140.5, 128.6-138.0, 126.3-134.9, 120.2-125.3 and 110.6-119.8 mAh / g, respectively. At the same time, under 1C@100 cycles, the capacity retention rate can be maintained at 86.1-90.2%. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a scanning electron microscope (SEM) image of the Cu-NMHFC@PAN prepared in Example 1;

[0021] Figure 2 X-ray diffraction (XRD) pattern of Cu-NMHFC@PAN prepared in Example 1;

[0022] Figure 3 This is the rate performance diagram of Cu-NMHFC@PAN prepared in Example 1;

[0023] Figure 4 The cycling stability of Cu-NMHFC@PAN prepared in Example 1 at 1C. DETAILED DESCRIPTION

[0024] The present invention is described in detail below in conjunction with the examples and comparative examples, but the present invention is not limited thereto. The radio frequency heating device used in a specific embodiment of the present invention is China Shuangping SPG-10-II. Example 1

[0025] (1) dissolving sodium ferrocyanide in 20 mL of deionized water to obtain a light yellow first solution (wherein the molar concentration of sodium ferrocyanide is 0.1 mol / L); dissolving manganese sulfate, copper sulfate, and polyvinyl pyrrolidone in the first solution to prepare a precursor suspension (wherein the molar concentration of manganese sulfate is 0.05 mol / L, the molar ratio of copper ion to manganese ion is 1:9, and the molar ratio of manganese ion to polyvinyl pyrrolidone is 1:1);

[0026] (2) The precursor suspension is transferred to a radio frequency heating device, and the device is started for moderate radio frequency heating treatment and aging (operating frequency of 800 kHz, output current of 22 A, reaction temperature of 70°C, reaction time of 5 h, aging of 3 h), and then washed with a water detergent to obtain a Prussian blue wet material;

[0027] (3) Adding a dimethylformamide solution of polyacrylonitrile to the Prussian blue wet material obtained in step (2) and continuing to perform moderate radio frequency heating treatment (the mass of polyacrylonitrile accounts for 3% of the total mass of the polyacrylonitrile, the Prussian blue wet material and the dimethylformamide), followed by centrifugation and vacuum drying (centrifugal speed of 8000 rpm, drying temperature of 60°C, time of 6 h), and then grinding after keeping at room temperature for 12 h to obtain a polyacrylonitrile-coated copper-doped manganese-based Prussian blue positive electrode material (Cu-NMHFC@PAN).

[0028] In this embodiment, Cu-NMHFC@PAN is obtained, the particle size of the positive electrode material is 0.22-1.37 μm, the grains are angular, and the angularity is clear. The atomic ratio of Mn to Cu measured by inductively coupled atomic emission spectroscopy (ICP-AES) is 9.10. Example 2

[0029] (1) dissolving sodium ferrocyanide in 20 mL of deionized water to obtain a light yellow first solution (wherein the molar concentration of sodium ferrocyanide is 0.45 mol / L); dissolving manganese acetate, copper chloride, and ascorbic acid in the first solution to prepare a precursor suspension (wherein the molar concentration of manganese sulfate is 0.08 mol / L, the molar ratio of copper ion to manganese ion is 1:3, and the molar ratio of manganese ion to ascorbic acid is 1:3);

[0030] (2) The precursor suspension is transferred to a radio frequency heating device, and the device is started for moderate radio frequency heating treatment and aging (the operating frequency of the radio frequency heating machine is 700 kHz, the output current is 20 A, the reaction temperature is 90°C, the reaction time is 6 hours, and the aging time is 4 hours), and then cleaned with an ethanol cleaning agent to obtain a Prussian blue wet material;

[0031] (3) Adding the polyacrylonitrile sulfolane solution to the Prussian blue wet material obtained in step (2) and continuing to perform moderate radio frequency heating treatment (the mass of the polyacrylonitrile accounts for 5% of the total mass of the polyacrylonitrile, the Prussian blue wet material and the sulfolane amine), then removing the solvent and vacuum drying (centrifugal speed of 10000 rpm, drying temperature of 95 ° C, time of 10 h), and then keeping it at room temperature for 6 h and grinding it to obtain Cu-NMHFC@PAN.

[0032] In this embodiment, Cu-NMHFC@PAN is obtained, and the particle size of the positive electrode material is 0.51-0.95 μm. The atomic ratio of Mn to Cu measured by ICP-AES is 2.92. Example 3

[0033] (1) dissolving sodium ferrocyanide in 20 mL of deionized water to obtain a light yellow first solution (wherein the molar concentration of sodium ferrocyanide is 0.5 mol / L); dissolving manganese chloride, copper nitrate, and citric acid in the first solution to prepare a precursor suspension (wherein the molar concentration of manganese sulfate is 0.1 mol / L, the molar ratio of copper ions to manganese ions is 1:1, and the molar ratio of manganese ions to citric acid is 1:2);

[0034] (2) The precursor suspension was transferred to a radio frequency heating device, and the device was started for moderate radio frequency heating treatment and aging (the operating frequency of the radio frequency heating machine was 760 kHz, the output current was 23 A, the reaction temperature was 60 ° C, the reaction time was 3 h, and the aging time was 2 h), and then the Prussian blue wet material was obtained by washing with an ethanol cleaning agent;

[0035] (3) Adding a dimethyl sulfoxide solution of polyacrylonitrile to the Prussian blue wet material obtained in step (2) and continuing to perform moderate radio frequency heating treatment (the mass of polyacrylonitrile accounts for 10% of the total mass of the polyacrylonitrile, Prussian blue wet material and dimethyl sulfoxide), then removing the solvent and vacuum drying (centrifugal speed of 12000 rpm, drying temperature of 100°C, time of 8 hours), and then grinding after keeping at room temperature for 24 hours to obtain Cu-NMHFC@PAN.

[0036] In this embodiment, Cu-NMHFC@PAN is obtained, and the particle size of the positive electrode material is 0.3-0.83 μm. The atomic ratio of Mn to Cu measured by ICP-AES is 0.95. Example 4

[0037] (1) dissolving sodium ferrocyanide in 20 mL of deionized water to obtain a light yellow first solution (wherein the molar concentration of sodium ferrocyanide is 0.2 mol / L); dissolving manganese nitrate, copper sulfate, and trisodium citrate in the first solution to prepare a precursor suspension (wherein the molar concentration of manganese sulfate is 0.2 mol / L, the molar ratio of copper ion to manganese ion is 1:5, and the molar ratio of manganese ion to ascorbic acid is 1:5);

[0038] (2) Transferring the precursor suspension to a radio frequency heating device, starting the device for moderate radio frequency heating treatment and aging (the operating frequency of the radio frequency heating machine is 900 kHz, the output current is 25 A, the reaction temperature is 70°C, the reaction time is 4 hours, and the aging time is 6 hours), and then washing with a water detergent to obtain a Prussian blue wet material;

[0039] (3) Adding a dimethylformamide solution of polyacrylonitrile to the Prussian blue wet material obtained in step (2) and continuing to perform moderate radio frequency heating treatment (the mass of polyacrylonitrile accounts for 6% of the total mass of the polyacrylonitrile, Prussian blue wet material and dimethylformamide), then removing the solvent and vacuum drying (centrifugal speed of 9000 rpm, drying temperature of 120°C, time of 6 h), and then grinding after keeping at room temperature for 18 h to obtain Cu-NMHFC@PAN.

[0040] In this embodiment, Cu-NMHFC@PAN is obtained, and the particle size of the positive electrode material is 0.67-1.37 μm. The atomic ratio of Mn to Cu measured by ICP-AES is 5.02. Comparative Example 1

[0041] In this comparative example, no copper source was added, and the other processes were consistent with those in Example 1.

[0042] The particle size of the positive electrode material in this comparative example is 0.35-1.25 μm. Comparative Example 2

[0043] In this comparative example, polyacrylonitrile was not added, and the other processes were the same as those in Example 1.

[0044] In this embodiment, Cu-NMHFC@PAN is obtained, the particle size of the positive electrode material is 0.10-1.05 μm, and the molar ratio of Mn to Cu measured by ICP-AES is 9.06. Comparative Example 3

[0045] In this comparative example, ordinary chemical coprecipitation method was adopted for synthesis, and the detailed steps are as follows.

[0046] (1) Sodium ferrocyanide and 20 mL of deionized water are mixed to obtain a light yellow first solution (wherein the molar concentration of sodium ferrocyanide is 0.1 mol / L); manganese sulfate, copper sulfate, and polyvinyl pyrrolidone are dissolved in 20 mL of deionized water to obtain a second solution (wherein the molar concentration of manganese sulfate is 0.05 mol / L, the molar ratio of copper ion to manganese ion is 1:9, and the molar ratio of manganese ion to polyvinyl pyrrolidone is 1:1);

[0047] (2) mixing the first solution and the second solution to perform a coprecipitation reaction, and then removing the supernatant to obtain a Prussian blue wet material (reaction temperature: 70°C, reaction time: 5h, aging: 3h);

[0048] (3) Add a dimethylformamide solution of polyacrylonitrile to the Prussian blue wet material and stir (the mass of polyacrylonitrile accounts for 3% of the total mass of the polyacrylonitrile, Prussian blue wet material and dimethylformamide), then centrifuge and vacuum dry (centrifugal speed is 8000 rpm, drying temperature is 60°C, time is 6 h), cool to room temperature and grind to obtain polyacrylonitrile-coated copper-doped manganese-based Prussian blue positive electrode material (Cu-NMHFC@PAN).

[0049] In this embodiment, Cu-NMHFC@PAN is obtained, the particle size of the positive electrode material is 0.45-1.60 μm, and the molar ratio of Mn to Cu measured by ICP-AES is 8.80.

[0050] Performance Test:

[0051] The positive electrode material obtained according to the embodiment and the comparative example was homogenized in the ratio of active component: conductive agent: PVDF = 7:2:1 to prepare a positive electrode sheet, a metal sodium sheet was used as a counter electrode, a 1 mol / L NaPF6 (EC / DEC=1 / 1) solution was used as an electrolyte, and a Whatman adhesive-free glass fiber filter paper was used as a diaphragm. A 2032-type button cell was assembled in an argon atmosphere glove box, and the voltage test range was 2.0-4.0V. The test results are shown in Table 1:

[0052]

[0053] The Cu-NMHFC@PAN cathode material obtained in Example 1 was tested by scanning electron microscopy, and the obtained SEM image is as follows: Figure 1 This test revealed the unique advantages of radio frequency heating technology in the synthesis of Prussian blue crystals, which can precisely control the size and morphology of the crystals while promoting the uniform formation of the polyacrylonitrile coating. Figure 1 It can be seen that the Cu-NMHFC@PAN cathode material obtained in Example 1 has a relatively regular morphology, but no clear cubic shape. This morphological feature indicates that there is a polyacrylonitrile coating layer on the surface of the cathode material. This coating layer not only effectively prevents the sensitivity of NMHFC to external oxygen and water vapor, reduces the generation of internal crystal water and Fe(CN)6 defect vacancies, but also inhibits the formation of Mn 2+ The dissolution of ions enhances the material's cycle stability and capacity retention; in addition, the uniform heating characteristics of the RF heating technology avoid local overheating and help form high-quality Prussian blue crystals, which is crucial for improving the electrochemical performance of the material. The particle size of the material is in the range of 0.22 to 1.37 μm, showing good dispersibility, which further confirms the superiority of RF heating technology in synthetic uniformity.

[0054] The Cu-NMHFC@PAN cathode material obtained in Example 1 was subjected to XRD test. Figure 2 As shown. Figure 2 It can be seen that the diffraction peak of the Cu-NMHFC@PAN cathode material obtained in Example 1 is steep and sharp and has no impurity peaks, indicating that the product has good crystallinity and high purity.

[0055] The prepared Cu-NMHFC@PAN cathode material was subjected to electrochemical tests, such as Figure 3 and 4 As shown. The specific capacities of the Cu-NMHFC@PAN cathode material prepared in Example 1 at current densities of 0.1, 0.2, 0.5, 1, 2 and 5C are 157.8, 140.5, 138.0, 134.9, 125.3 and 119.8 mAh / g, respectively. Even after 100 cycles at 1C, the capacity retention rate reaches 90.2%, showing excellent charge and discharge performance and cycle stability. The same test was performed on the materials of Examples 2 to 4, and the results were similar to those of Example 1 (Table 1). The difference in capacity retention of the samples in each example at a current density of 1C did not exceed 4.1%.

[0056] Compared with the sample in comparative example 1, example 1 has better performance under rate and 1C@100 cycle conditions, indicating that copper doping successfully regulates the lattice structure of manganese-based Prussian blue, improves its electrical conductivity, and improves the low-spin Fe 2+ / Fe 3+ Coupled redox activation, thereby achieving a greater capacity contribution at a higher voltage. As for Comparative Example 2, since no polyacrylonitrile coating layer was added, the material was kept at room temperature for 12 hours, which resulted in a high content of crystal water and Fe(CN)6 defect vacancies inside, and it also failed to prevent Mn 2+ Dissolved in liquid electrolyte, which significantly reduces the cycle reversibility and capacity retention. In addition, the traditional coprecipitation method used in Comparative Example 3 failed to accurately control the size and morphology of Prussian blue crystals, resulting in a generally large particle size and increased ion diffusion paths, which may not only reduce the battery's charge and discharge rate and ion conductivity, but also may cause battery performance degradation and reduced cycle stability due to structural changes during the charge and discharge process.

[0057] The above-described specific embodiments further illustrate the present invention in detail, but these descriptions cannot be understood as limiting the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a polyacrylonitrile-coated copper-doped manganese-based Prussian blue positive electrode material, characterized in that: The steps include: (1) dissolving sodium ferrocyanide in deionized water, and adding a manganese source, a copper source, and a chelating agent thereto to obtain a precursor suspension; (2) transferring the precursor suspension to a radio frequency heating device, performing moderate radio frequency heating treatment and aging, and then washing with a cleaning agent to obtain a Prussian blue wet material; (3) adding the Prussian blue wet material obtained in step (2) to a solution of polyacrylonitrile in an organic solvent, continuing to perform moderate radio frequency heating treatment, then centrifuging and vacuum drying, keeping at room temperature for a period of time, and then grinding to obtain a polyacrylonitrile-coated copper-doped manganese-based Prussian blue positive electrode material; In the step (1), the manganese source is one of manganese chloride, manganese sulfate, manganese nitrate or manganese acetate, the copper source is one of copper sulfate, copper chloride or copper nitrate, and the chelating agent is one of ascorbic acid, citric acid, trisodium citrate or polyvinyl pyrrolidone; the ferrocyanide concentration is 0.1-0.5 mol / L, the manganese ion concentration is 0.05-0.2 mol / L, the molar ratio of copper ion to manganese ion is 1:1-9, and the molar ratio of manganese ion to chelating agent is 1:1-5; In the step (2), the operating frequency of the radio frequency heating device is 700-900 kHz, the output current is 20-25 A, the reaction temperature is 60-90° C., the reaction time is 3-6 hours, and the aging time is 2-6 hours; the cleaning agent is water or ethanol; In the step (3), the organic solvent is one of dimethylformamide, dimethyl sulfoxide or cyclopentane sulfone, and the mass of polyacrylonitrile accounts for 3% to 10% of the total mass of the polyacrylonitrile, Prussian blue wet material and the organic solvent; the operating frequency, output current, reaction temperature, reaction time and aging time of the radio frequency heating device are consistent with those of step (2); the centrifugal speed is 6000 to 12000 rpm, the drying temperature is 60 to 120°C, and the time is 6 to 10 hours; and the drying is maintained at room temperature for 6 to 24 hours.

2. A polyacrylonitrile coated copper-doped manganese-based Prussian blue positive electrode material prepared by the preparation method according to claim 1, characterized in that: The particle size of the positive electrode material is 0.22-1.37 μm, the atomic ratio of Mn to Cu is 0.95-9.10, the positive electrode material is in a cubic shape, and the crystal grains have edges and corners.

3. An application of the polyacrylonitrile coated copper-doped manganese-based Prussian blue positive electrode material as claimed in claim 2, characterized in that: The polyacrylonitrile-coated copper-doped manganese-based Prussian blue positive electrode material is used as the positive electrode of a sodium ion battery.

Citation Information

Patent Citations

  • High-stability sodium ion battery positive electrode material and preparation thereof

    CN117133867A

  • Cation-doped manganese-based Prussian blue positive electrode material for sodium ion battery and preparation method of positive electrode material

    CN117239117A

  • Preparation method of PVP modified prussian blue nanometer material

    CN108324733A

  • Conductive polymer coated Prussian blue sodium ion battery positive electrode material and preparation method thereof

    CN110224130A

  • Preparation method and application of ternary metal Prussian blue positive electrode material

    CN115172741A